Analisis Perilaku Konsumtif Masyarakat Dalam Perspektif Ekonomi Syariah Di Desa Lalonggombu Kecamatan Lainea Kabupaten Konawe Selatan - Murni Nia; Murniati Murniati; Wahyu Muh. Syata; Yuli Regina Tasman (Indo Publishing, 2026)
This study aims to analyze the consumptive behavior of the community in Lalonggombu Village, Lainea District, Konawe Selatan Regency from an Islamic economic perspective. This study employs a qualitative approach with a descriptive method to explore in depth the phenomenon of consumptive behavior within the community. Data were collected through interviews, observations, and documentation involving village residents as informants. The results show that the community’s consumptive behavior is characterized by a tendency to make excessive and unplanned purchases, as well as prioritizing wants over needs. Factors influencing this behavior include ease of access to goods, social environmental influences, and the presence of attractive promotional offers. From an Islamic economic perspective, such consumptive behavior is not fully in line with Islamic consumption principles, which emphasize moderation, avoidance of extravagance (israf), and prioritization of needs over desires.In conclusion, the consumptive behavior of the community in Lalonggombu Village reflects a deviation from Islamic economic principles in managing consumption. Therefore, it is necessary to enhance public awareness and understanding of the importance of applying Islamic economic values in consumption activities in order to achieve a balance between worldly needs and spiritual values.